Molluscicidal activity and inhibition of acetylcholinesterase activity of azadirachta indica extract on Pomacea canaliculate - Nik Amalia Nasratiena Mat Zaib,; Saiyidah Nafisah Hashim,; Wan Rozianoor Mohd Hassan,; Chia, Chay Tay (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Golden Apple Snail, Pomacea canaliculata, is a notorious pest in Malaysia, leading to substantial agricultural and economic losses, while, the neem tree, Azadirachta indica has been identified as alternative source for bio-pesticides. There is currently limited information on A. indica as natural molluscicide against P. canaliculata. This study aims to evaluate the effects of A. indica on P. canaliculata at various life stages (eggs, juvenile and adult). The bioactive compound, azadirachtin in A. indica extracts was quantified using high-performance liquid chromatography (HPLC). Egg hatchability was determined using spot spraying on egg clusters while the molluscicidal activity of A. indica on juvenile and adult specimens was evaluated using the immersion bioassay approach. The snail’s acetylcholinesterase (AChE) inhibition was assessed using Ellman assay. The azadirachtin content in the ethanolic extract of A. indica leaves at a concentration of 1 µg/mL was found to be 45.42%. Increasing the concentration of A. indica extracts resulted in lower egg hatchability and increased mortality of juvenile and adult snails. Azadirachta indica extracts showed the highest effectiveness against adult P. canaliculata with an LC50 value of 0.52 mg/mL, compared to 0.92 mg/mL for juveniles and 0.74 mg/mL for eggs. Additionally, A. indica extract exhibited greater inhibition of AChE in adult specimens compared to juvenile specimens and eggs. The IC50 for adult is 0.60 μg/mL, which is the lowest while the IC50 for juvenile is 0.68 μg/mL, the highest. Taken together, A. indica shows immerse potential as natural pesticide for managing the population of P. canaliculata.